THE EFFECT OF CAREER DEVELOPMENT AND INCENTIVES ON EMPLOYEE WORK LOYALTY - Juwita Magdalena Sitanggang; Immanuel Edy Suranta Sebayang; Hidayat Nasution (PT. MITRA ANGKASA INFORMATIKA, 2024)
Loyalty is an attitude that shows employee loyalty and is an ongoing process of how an organization member expresses their attention to the success and goodness of the organization. If a person's loyalty is high then his performance will be better. Many factors affect employee work loyalty including career development and providing incentives. This study is to determine the effect of career development and incentives for employee loyalty both partially and simultaneously. Based on the research objectives, this type of research can be divided into quantitative and qualitative research types. The object of this research is the employees of PT. Aneka Karya Duta Medan, amounting to 65 people. The sampling technique uses a saturated sampling technique which means the population is the same as the sample. The data analysis technique used is multiple regression analysis. The results showed partially and simultaneously career development and the provision of incentives had an effect on employee work loyalty at PT. Various Works of Medan Ambassadors. The company is advised to promote employees, be fair to every employee, allow employees to take part in training to improve their careers, give bonuses to employees who excel, give commissions to employees who successfully achieve the set targets, give profit share every year if the company manages to achieve the set sales targets, give awards for the achievements achieved by employees and give praise for the achievements given by employees to the company. Keywords : Career Development, Giving Incentives and Work Loyalty